2013
DOI: 10.1093/nar/gkt410
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP1 promotes mesenchymal cell properties and migration of tumor-derived cells by enhancing the expression of LEF1 and SNAI2 (SLUG)

Abstract: The oncofetal IGF2 mRNA-binding protein 1 (IGF2BP1) controls the migration and invasiveness of primary as well as tumor-derived cells in vitro. Whether the protein also modulates epithelial-mesenchymal-transition (EMT), a hallmark of tumor progression involved in tumor cell dissemination, remained elusive. In this study, we reveal that IGF2BP1 enhances mesenchymal-like cell properties in tumor-derived cells by promoting the expression of the transcriptional regulators LEF1 and SLUG (SNAI2). IGF2BP1 associates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 50 publications
5
57
0
Order By: Relevance
“…Several reports have indicated that LEF1 induces EMT in PCa cells (18, 37, 38). Here we sought to determine whether miR-34a, via LEF1, regulates EMT, migration and invasion of PCa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have indicated that LEF1 induces EMT in PCa cells (18, 37, 38). Here we sought to determine whether miR-34a, via LEF1, regulates EMT, migration and invasion of PCa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we found a substantial decrease in expression of IGF2BP2 after wounding in transgenic mice, providing a possibility that IGF2BP2 could maintain skin tissue homoeostasis by promoting the migration of keratinocyte. Many studies illustrated that IGF2BPs may enhance the formation of lamellipodia, enforce intrinsic polarization and thus promote cell migration in tumor cell dissemination . The function of IGF2BP1 is well known to promote cell migration, but the exact function of IGF2BP2 is still not clear and needs to be fully elucidated in cutaneous wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, cells were co-transfected with a SNAI2 -promoter containing luciferase promoter construct (kindly provided by S. Hüttelmaier; (30) together with a plasmid expressing Renilla luciferase (pRL-TK, Promega) and either an empty control vector (pSG5) or KLF10 expression vector. Firefly luciferase activity was normalized to Renilla luciferase activity to control for transfection efficiency.…”
Section: Methodsmentioning
confidence: 99%